Delmira, Alfonsina, Juana y Gabriela: intertextualidades - Fernández dos Santos, Mirta (2016)
Delmira Agustini has been considered by critics a precursor of poetry written by women in the Río de la Plata literary context at the beginning of the 20th century, and also as an undeniable reference for other Latin American women poets: Alfonsina Storni, Juana de Ibarbourou and Gabriela Mistral. In addition to the coincidences identified regarding mutual influences that exist among the three big women poets of the Southern Cone, each of them wrote about Delmira Agustinis tutelage. Thus, the aim of this paper is to unveil some unpublished documents and to retrieve others that are not widely read. In these writings, I will demonstrate how Storni, Ibarbourou and Mistral reveal the influence exerted by Agustini in shaping their poetic identities.